Factors of trade in Europe - Jan Hanousek; Evžen Kočenda (Institut für Ost- und Südosteuropaforschung (IOS), 2013)
We analyze how a set of traditional as well as new determinants affect trade among European countries over the period 1992-2008. The factors encompass variables from the areas of geography, culture, institutions, infrastructure, and trade direction. Trade is analyzed for three types of goods: primary goods, parts and components, and capital goods. For each type of good we also distinguish its definition in terms of flows, intensive margin, and extensive margin. Methodologically we first derive country-pair fixed effects over all possible pairs of export-import partners, and in the second stage we relate fixed effects with a set of influential factors. We show (i) the intuitive and varying effects of geographical, cultural, and institutional factors, (ii) the beneficial effects of soft and hard infrastructure, and (iii) the key importance of the trade between old and new EU members.
urn:nbn:de:101:1-20130819101
Keywords: F14; F16; L24; 330; bilateral trade; factors of trade; panel data; European Union